The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/ijgi5020013
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Method for Interpolating Missing Data in Heterogeneous Spatio-Temporal Datasets

Abstract: Space-time interpolation is widely used to estimate missing or unobserved values in a dataset integrating both spatial and temporal records. Although space-time interpolation plays a key role in space-time modeling, existing methods were mainly developed for space-time processes that exhibit stationarity in space and time. It is still challenging to model heterogeneity of space-time data in the interpolation model. To overcome this limitation, in this study, a novel space-time interpolation method considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…It has been found that the accuracy of the monitoring results obtained by the automatic gravimetric method meets the requirements of the standard manual monitoring method (Cheng, Gong, & Pan, ). To reduce the effect of missing data on the prediction results, a dataset with fewer missing values was selected, and some individual missing values were estimated using a spatio‐temporal interpolation method (Deng et al, ). Figure shows the spatial distribution of these monitoring sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the accuracy of the monitoring results obtained by the automatic gravimetric method meets the requirements of the standard manual monitoring method (Cheng, Gong, & Pan, ). To reduce the effect of missing data on the prediction results, a dataset with fewer missing values was selected, and some individual missing values were estimated using a spatio‐temporal interpolation method (Deng et al, ). Figure shows the spatial distribution of these monitoring sites.…”
Section: Resultsmentioning
confidence: 99%
“…The non‐separated approach aims to define a joint space–time covariance structure (Heuvelink & Griffith, ). When a space–time covariance structure is defined, kriging methods can be used to obtain the best linear unbiased prediction at a given location by computing a weighted average of the known values at its neighboring sites (Deng, Fan, Liu, & Gong, ). Although space–time dependence is considered in space–time geostatistics, the nonlinearities and nonstationarities of a space–time series cannot be well handled by space–time geostatistics.…”
Section: Related Workmentioning
confidence: 99%
“…To compare different imputation models with cross-validation, we used three indices to measure the actual prediction accuracy, namely, the standardized allocation error (SAE) 11 , the mean square error (MSE) and the coefficient of determination (R 2 ) 21 , 35 . All these indices compare the model-predicted values with observed values.…”
Section: Methodsmentioning
confidence: 99%
“…The R 2 is an index for assessing the agreement between observed and estimated values, with the value ranging from 0 for complete disagreement to 1 for perfect agreement. Scatterplots were created to compare the observed values and estimated values in the cross-validation 1 , 21 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation